“I Think the Mental Part Is the Biggest Factor”: An Exploratory Qualitative Study of COVID-19 and Its Negative Effects on Indigenous Women in Toronto, Canada - Flores, Jerry; Emory, Kristen; Santos, Xuan; Mashford-Pringle, Angela; Barahona-Lopez, Kati; Bozinovic, Keston; Adams, Jennifer; Chen, Coco; Zuo, Yandy; Nguyen, Diana (Frontiers in Sociology, 2022)
This article explores the unique and understudied experiences of Indigenous women living in Toronto, Canada during the first year of the COVID-19 pandemic. The purpose of this study is to better document the impacts of COVID-19 on the mental health and well-being of Indigenous women in Toronto, Canada to better understand unmet needs, as well as lay the groundwork for more targeted research and potential interventions based on these needs. Using in-depth semi-structured interviews with thirteen Indigenous women, we shed light on the negative effects this pandemic has had on this population. We find that COVID-19 has negatively affected people’s mental health, substance use and access to health services. This research speaks to the growing body of work that discusses the harmful effects of COVID-19 generally and how this pandemic has specifically affected Indigenous peoples.